2016
DOI: 10.1016/j.msea.2015.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Damage evolution and failure mechanisms in additively manufactured stainless steel

Abstract: In situ tensile tests were performed on additively manufactured austenitic stainless steel to track damage evolution within the material. For these experiments Synchrotron Radiation micro-Tomography was used to measure three-dimensional pore volume, distribution, and morphology in stainless steel at the micrometer length-scale while tensile loading was applied. The results showed that porosity distribution played a larger role in affecting the fracture mechanisms than measured bulk density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(109 citation statements)
references
References 32 publications
7
90
0
6
Order By: Relevance
“…Other nondestructive methods, such as acoustic emission (AE) and electrical resistance have been utilized to study the types of damage that occur in CMCs under various types of loading and environmental conditions . The use of X‐ray computed microtomography to observe damage in various types of CMCs has proven to be a valuable nondestructive techniques …”
Section: Introductionsupporting
confidence: 90%
“…Other nondestructive methods, such as acoustic emission (AE) and electrical resistance have been utilized to study the types of damage that occur in CMCs under various types of loading and environmental conditions . The use of X‐ray computed microtomography to observe damage in various types of CMCs has proven to be a valuable nondestructive techniques …”
Section: Introductionsupporting
confidence: 90%
“…It should be noted that the distribution of the porosity, size, and morphology is not homogeneous, and local porosity concentrations could be much higher than the global porosity, which makes the locations with the highest porosity, containing defects with the largest size, or aspect ratio more vulnerable during loading. Hence, controlling and minimizing defects is challenging.…”
Section: Features Of Metal Ammentioning
confidence: 99%
“…Designed porosity is present only in lattice structures while undesigned porosity is found commonly in all AM parts. Another example was presented in the recent paper by Carlton et al [80], in which the authors performed tensile tests of SLM as-built and annealed 316L stainless steel in-situ during white light synchrotron XCT. This experiment showed that the role of the porosity distribution is larger than the role of bulk density in affecting fracture mechanisms.…”
Section: Recent Novel Xct Porosity Measurementsmentioning
confidence: 99%